Ethnic and generational differences in traditional knowledge and the cultural importance of Lannea microcarpa Engl. & K. Krause in the Sudanian savannah of Benin - Goudégnon ., Eude Oré Adédiran; Vodouhê, Fifanou G.; Gouwakinnou, Gérard Nounagnon; Oumorou, Madjidou (My University, 2017)
Understanding the socio-cultural importance of indigenous fruit trees (IFT) and its determining factors is a prerequisite for developing their value and making management decisions. This study documented traditional knowledge (TK) and the cultural importance (CI) of Lannea microcarpa, a neglected and underused indigenous fruit tree found in Benin’s Sudanian region. The study further tested whether TK and CI varied according to ethnic groups and generations. We collected data on the uses and importance of the species from 262 informants who were randomly selected within its zone of occurrence, using free lists and scoring, respectively. Twenty-eight specific uses were reported, of which 21 were medicinal, 2 were commercial, and 1 each was for food, fodder, firewood, construction, packaging and toothpicks. Contrary to the other use categories, traditional knowledge on food uses did not vary either between generations or among ethnic groups. In addition, food use was culturally the most important, followed by medicinal uses. Overall, the fruit was the preferred and most frequently commercialised part of the plant. Medical conditions treated with L. microcarpa include anaemia, diarrhoea, coughs, ulcers, stomach aches and blood evacuation after childbirth. Our findings suggest that domestication of L. microcarpa should prioritise the fruit, which is the most valued part of the plant. Further studies should therefore focus on the domestication potential of L. microcarpa for its fruit traits and on how to improve fruit production. Keywords: Lannea microcarpa, folk knowledge, development of fruit species, Sudanian zone, Benin. RESUMEN VARIACIONES GENERACIONALES Y ÉTNICAS EN EL CONOCIMIENTO TRADICIONAL Y EN LA IMPORTANCIA CULTURAL DE LANNEA MICROCARPA ENGL. & K. KRAUSE EN LA SABANA SUDANESA DE BENÍN Conocer la importancia sociocultural de los árboles frutales autóctonos y los factores que la determinan es una condición previa imprescindible para tomar decisiones sobre la valorización y el manejo. Este estudio documentó el conocimiento tradicional (CT) y la importancia cultural (IC) de Lannea microcarpa, un frutal autóctono poco conocido e infrautilizado de la zona sudanesa de Benín. El estudio también analizó las posibles variaciones del CT y la IC entre grupos étnicos y generacionales. Mediante el método de listados libres y un sistema de puntuación, se recogió información sobre los usos e importancia de la especie entre 262 personas seleccionadas al azar en la zona de distribución del árbol. Se registraron veintiocho usos, 21 de los cuales eran medicinales, 2 comerciales y uno para cada una de las categorías siguientes: alimentación, forraje, leña, construcción, embalaje y palillos de dientes. Al contrario de las demás categorías de usos, los conocimientos tradicionales relacionados con los usos alimentarios no varían según las generaciones o grupos étnicos. Además, los usos alimentarios son los más importantes culturalmente, seguidos por los usos medicinales. En general, el fruto es la parte preferida del árbol y la que más se comercializa. Los problemas de salud tratados con L. microcarpa comprenden la anemia, diarrea, tos, úlceras, dolores estomacales y hemorragias postparto. Estos resultados sugieren que se debe priorizar el fruto, la parte más apreciada del árbol, en la domesticación de L. microcarpa. Los posteriores estudios podrán analizar las posibilidades de domesticación de L. microcarpacentrán
Keywords: Lannea microcarpa; folk; knowledge; development of fruit species; Sudanian zone; Benin.